Functional Outcomes Following Microfragmented Adipose Tissue Versus Bone Marrow Aspirate Concentrate Injections for Symptomatic Knee Osteoarthritis. (21st July 2019) - Mautner, Kenneth; Bowers, Robert; Easley, Kirk; Fausel, Zachary; Robinson, Ryan
Abstract: This study aimed to determine whether autologous orthobiologic tissue source affects pain and functional outcomes in patients with symptomatic knee osteoarthritis (OA) who received microfragmented adipose tissue (MFAT) or bone marrow aspirate concentrate (BMAC) injection. We retrospectively reviewed prospectively collected data from patients who received BMAC or MFAT injection for symptomatic knee OA. Patients completed baseline and follow-up surveys. Each survey included the Knee Injury and Osteoarthritis Outcome Score (KOOS) questionnaire, Emory Quality of Life (EQOL) questionnaire, and Visual Analog Scale (VAS) for pain. The follow-up responses were compared with baseline for all patients and between BMAC and MFAT groups. A total of 110 patients met inclusion criteria, with 76 patients (BMAC 41, MFAT 35) and 106 knees (BMAC 58, MFAT 48) having appropriate follow-up data. The BMAC group included 17 females and 24 males, with a mean age of 59 ± 11 years. The MFAT group included 23 females and 12 males, with a mean age of 63 ± 11 years. Minimum follow-up time was 0.5 years. Mean follow-up time was 1.80 ± 0.88 years for BMAC and 1.09 ± 0.49 years for MFAT. Both groups had significant improvement in EQOL, VAS, and all KOOS parameters preprocedure versus postprocedure ( p  < .001). There was not a significant difference when comparing postprocedure scores between groups ( p = .09, .38, .63, .94, .17, .15, .70, respectively). These data demonstrate significant improvement in pain and function with both MFAT and BMAC injections in patients with symptomatic knee OA without a significant difference in improvement when comparing the two autologous tissue sources. Stem Cells Translational Medicine   2019;8:1149–1156 : Abstract : Patients with symptomatic knee osteoarthritis received injections of either bone marrow aspirate concentrate (BMAC) or microfragmented adipose tissue (MFAT). Pain and function improved significantly in both groups without a significant difference in outcomes between the two treatments.